Linya at galaw (mga dula sa Filipino at Ingles) - Torres, Jose Victor Z. (Manila, Philippines University of Santo Tomas Publishing House, 2023)
Collection of plays in Filipino and English.
Relasyon -- Monologo -- Kasaysayan.
Text in Filipino and English.
Keywords: Filipino drama; Philippine drama (English)